Insulin Resistance Exacerbates Alzheimer Disease via Multiple Mechanisms - Wei, Zenghui; Koya, Jagadish; Reznik, Sandra E. (Frontiers in Neuroscience, 2021)
Alzheimer’s disease (AD) is a chronic neurodegenerative disease that accounts for 60-70% of dementia and is the sixth leading cause of death in the United States. The pathogenesis of this debilitating disorder is still not completely understood and there is no drug therapy that prevents or reverses AD. New insights into the pathogenesis of AD are needed in order to develop novel pharmacologic approaches. In recent years, numerous studies have shown that insulin resistance plays a significant role in the development of AD. Over 80% of patients with AD have type II diabetes (T2DM) or abnormal serum glucose, suggesting that the pathogenic mechanisms of insulin resistance and AD likely overlap. Insulin resistance increases neuroinflammation, which promotes both Aβ deposition and aberrant tau phosphorylation. By increasing production of reactive oxygen species, insulin resistance triggers pro-Aβ cascades. Oxidative stress associated with insulin resistance also dysregulates glycogen synthase kinase 3-beta, which leads to increased tau phosphorylation. Both insulin and Aβ are metabolized by insulin degrading enzyme. Defects in this enzyme are the basis for a strong association between T2DM and AD. This review highlights multiple pathogenic mechanisms induced by insulin resistance that are implicated in AD. Several pharmacologic approaches to AD associated with insulin resistance are presented.